Neural Entrainment and Attentional Selection in the Listening Brain - Obleser, Jonas; Kayser, Christoph (Trends in cognitive sciences, 2019)
The streams of sounds we typically attend to abound in acoustic regularities. Neural entrainment is seen as an important mechanism that the listening brain exploits to attune to these regularities and to enhance the representation of attended sounds. We delineate the neurophysiology underlying this mechanism and review entrainment alongside its more pragmatic signature, often called ‘speech tracking’. The latter has become a popular analytical approach to trace the reflection of acoustic and linguistic information at different levels of granularity, from neurophysiology to neuroimaging. As we discuss, the concept of entrainment offers both a putative neurophysiological mechanism for selective listening and a versatile window onto the neural basis of hearing and speech comprehension. Electrophysiological studies suggest that entrainment of rhythmic activity can be a key mechanism to control neural sensory gain.Selective entrainment reflects exogenous stimulus attributes and the endogenous selection of task-relevant attended information.The neural tracking of multiple acoustic and linguistic features sheds light on their differential encoding and how they shape perception.Entrainment as a concept bridges across temporal and spatial scales of brain activity.